South Asia is far from achieving universal coverage of essential nutrition interventions: Examining coverage, trends, and inequities, 2005 to 2018 - Singh, Nishmeet; Nguyen, Phuong Hong; Scott, Samuel P.; Kim, Sunny S.; Neupane, Sumanta; Murira, Zivai; Heidkamp, Rebecca A.; Bhutta, Zulfiqar A.; Menon, Purnima; Torlesse, Harriet (American Society for Nutrition, 2020)
South Asia carries the largest burden of malnutrition globally. Tracking coverage of nutrition interventions is a critical step in designing effective nutrition policies and monitoring progress in the region. This paper examines coverage, trends, and inequities in nutrition interventions in South Asia.